2006
DOI: 10.1007/s00425-006-0303-3
|View full text |Cite
|
Sign up to set email alerts
|

Infection with virulent and avirulent P. syringae strains differentially affects photosynthesis and sink metabolism in Arabidopsis leaves

Abstract: Infection of plants with pathogens leads not only to the induction of defence reactions but also to changes in carbohydrate metabolism. In this study, the effects of infection by a virulent and an avirulent strain of P. syringae on spatio-temporal changes in photosynthesis were compared using chlorophyll fluorescence imaging. The maximum PSII quantum yield, effective PSII quantum yield and nonphotochemical quenching were decreased in Arabidopsis leaves infected with either strain. At the same time, the quantum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
199
4
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(217 citation statements)
references
References 47 publications
13
199
4
1
Order By: Relevance
“…For example, during sunflower cotyledon infection by the necrotrophic fungus Sclerotinia sclerotiorum, sucrose level was reduced by 100 %, fructose by 85 %, whereas for glucose it was only 20 % (Jobic et al 2007). Sugar levels decrease in tomato plants after inoculation with B. cinerea (Berger et al 2004;Bonfig et al 2006). Sugar deficit may lead to sugar starvation in cells, a phenomenon well characterized in terms of metabolism and at the gene expression level (Morkunas et al 2003).…”
Section: Sugar Sensing and Signalingmentioning
confidence: 99%
“…For example, during sunflower cotyledon infection by the necrotrophic fungus Sclerotinia sclerotiorum, sucrose level was reduced by 100 %, fructose by 85 %, whereas for glucose it was only 20 % (Jobic et al 2007). Sugar levels decrease in tomato plants after inoculation with B. cinerea (Berger et al 2004;Bonfig et al 2006). Sugar deficit may lead to sugar starvation in cells, a phenomenon well characterized in terms of metabolism and at the gene expression level (Morkunas et al 2003).…”
Section: Sugar Sensing and Signalingmentioning
confidence: 99%
“…Chloroplasts and mitochondria probably have other roles in plant/pathogen interactions in addition to ROS generation, particularly since both organelles are essential contributors to cell metabolism. Roles for metabolic interplay and sugar sensing in particular have been described in both virulent and avirulent plant/pathogen interactions (13). It has been suggested that photosynthesis and assimilatory metabolism are switched off in order to initiate respiration and defense reactions (12).…”
Section: Oxygen Deprivation Interferes With the Pcd Process By Limitimentioning
confidence: 99%
“…Exposure to abiotic stresses, such as drought, frequently causes inhibition of photosynthesis and accelerated ROS production (10). Pathogen attack causes suppression of photosynthetic gene expression (11) and a concomitant inhibition of photosynthesis (12,13), suggesting that light and ROS trigger common signaling pathways in plants exposed to abiotic and biotic stresses (14,15). Although ROS production by the mitochondrial ETC represents less than 1% of chloroplastic ROS generation in photosynthetic tissues (16), mitochondria have been proposed to be as important in the establishment of cell death in plants as they are in animals (17).…”
mentioning
confidence: 99%
“…At present, it is not clear if this stimulation of photosynthesis is due to the defence strategy of the plant (Berger et al, 2007). A decrease in photosynthesis has also been reported in incompatible interactions (Bonfig et al, 2006). The decrease in photosynthesis was detectable earlier with the avirulent strain than with the virulent strain.…”
Section: Photosynthesis and Pathogens Invasions 231 Photosynthesis mentioning
confidence: 89%
“…Theoretically, the photosynthetic capacity of plants is unlimited when the optimal growing conditions are met. Unfortunately, terrestrial plants are constantly challenged by abiotic (UV, water, salinity, temperature) (Baker et al, 1988, Baldry et al, 1966, Barhoumi et al, 2007, Barrow and Cockburn, 1982, Bassham, 1977, Batista-Santos et al, 2011, Bauerle et al, 2007, Berry, 1975, Bischof et al, 2000, Ripley et al, 2008, Ripley et al, 2007, Roberntz and Stockfors, 1998 and biotic (pathogens, pests, animal and human) stresses that reduce their productivity and even threaten their survival (Bilgin et al, 2010, Bonfig et al, 2006, Erickson and Hawkins, 1980, Garavaglia et al, 2010, Kocal et al, 2008. While the regulation of plant defence responses has been extensively investigated, the effects of pathogen infection on primary metabolism, including photosynthesis, are however less known.…”
Section: Introductionmentioning
confidence: 99%